2', 5'-oligoadenylate synthetase induction in lymphocytes of patients with connective tissue diseases. Issue 3 (March 1986) - Hylton, W; Cayley, J; Dore, C; Denman, A M
Abstract : Spontaneous production of the interferon induced enzyme 2', 5'-oligoadenylate synthetase (2', 5'-A synthetase) was significantly greater in blood lymphocytes of patients with systemic lupus erythematosus (SLE), Behçet's syndrome, and rheumatoid arthritis than in control lymphocytes. Alpha interferon (IFN-alpha) induced comparable production of enzyme in normal, rheumatoid, and Behçet's lymphocytes, and reduced, but still appreciable amounts in SLE lymphocytes. Phytohaemagglutinin (PHA) did not induce enzyme. Thus spontaneous production of 2', 5'-A synthetase is encountered in several connective tissue diseases and seems likely to be induced by in-vivo exposure to interferons.